2017
DOI: 10.17222/mit.2016.063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stainless-steel wire mesh on the mechanical behaviour in a glass-fibre-reinforced epoxy composite

Abstract: This work covers the fabrication and investigation of the mechanical behaviour of a glass-fibre-reinforced polymer (GFRP) composite embedded with a stainless-steel wire mesh (SSWM) layer. This work takes the hybridising approach in improving the mechanical properties of GFRP through the incorporation of SSWM into the laminates. The structure of the composite is such that the SSWM was placed in the top, middle and bottom of the GFRP. The laminates are fabricated using the hand-layup method with a 40 % weight fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Polymer matrix surrounding also eliminates additional measures for corrosion protection. 43,44 Briefly, due to their reasonable cost, ease of manufacturing, high E/q ratios and preventing catastrophic failure, they are good candidates for the applications in aviation, satellites, boat and yacht building, interior and exterior parts of the vehicles (e.g. corridor base, luggage compartments), etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer matrix surrounding also eliminates additional measures for corrosion protection. 43,44 Briefly, due to their reasonable cost, ease of manufacturing, high E/q ratios and preventing catastrophic failure, they are good candidates for the applications in aviation, satellites, boat and yacht building, interior and exterior parts of the vehicles (e.g. corridor base, luggage compartments), etc.…”
Section: Resultsmentioning
confidence: 99%
“…39 stacking the wire mesh stainless steel in sandwich structures has positively affected the bending rigidity of the specimens. Sakthivel and Vijayakumar 43 investigated the hybridisation effect of glass fibre/epoxy composite with stainless steel wire mesh sheets on mechanical properties in terms of tensile strength, flexural strength, inter delamination and low-velocity impact properties. It was concluded that energy absorption capacity and the cracking behaviour of the hybrid composite were enhanced and particularly the wire mesh layer embedded into the middle of the glass fibre/epoxy composite provided the best results.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Therefore, metal reinforcement elements in various forms such as film, continuous fiber, powders, and mesh have been added to the these composites to reduce their brittleness and provide ductility. [10][11][12][13][14] The mechanical properties of glass fibermetal reinforced epoxy hybrid composites have been investigated in several experimental studies. For example, McBride et al 10 experimentally investigated the hybrid composites made of unidirectional glass fabrics and steel fabrics that have different compositions, and indicated that as the number of glass fiber layers increased, the ultimate strength increased and the failure strain decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In the hybrid composite, the middle layer of wire mesh enhances the mechanical properties of the composite [25]. In the FRPC, the 45 � oriented wire mesh shows an increased stiffness, strength, and ductility [26]. The electro polished and etched layer exposed higher interface fracture toughness between the fiber and metal interface [27].…”
Section: Introductionmentioning
confidence: 99%